Order From Chaos: An Initiative to Improve Opioid Prescribing in Rheumatology Using Lean A3. Issue 9 (4th September 2019) - van Eeghen, Constance; Edwards, Melinda; Libman, Bonita S.; MacLean, Charles D.; Kennedy, Amanda G.
Abstract : Objective: Use an established quality improvement method, Lean A3, to improve the process of opioid prescribing in an academic rheumatology ambulatory clinic. Methods: This retrospective pre‐postintervention analysis of rheumatology records included patients prescribed opioids at least once during the study period. Lean A3 was used to develop a Controlled Substance Visit Protocol to standardize eight recommended elements of the opioid prescribing workflow. Analyses included changes in the recommended workflow elements and changes in opioid prescribing volume. Results: Improvements were observed in seven of the eight recommended elements. Patient education, including treatment agreements and consent forms (39% completion for both preimplementation) increased to 78% and 80%, respectively ( P < 0.001 for both). Risk assessment, as measured by the Current Opioid Misuse Measure, increased from 0.5% to 76% ( P < 0.001). Best practices in prescribing, including prescribing in multiples of seven to avoid weekend refill requests, increased from 1% to 79% ( P < 0.001). Monitoring parameters, including standardized functional assessment (0% vs. 86%), prescription drug monitoring program queries (49% vs. 84%), and urine testing (1% vs. 32%) all increased ( P < 0.001). Visits scheduled at least quarterly for patients on chronic opioids did not change ( P = 0.18). Overall, the number of patients prescribed opioids (185 vs. 160; P < 0.001) and annual prescription opioid morphine milligram equivalents (MMEs) (1 933 585 MME vs. 1 386 368 MME; P < 0.001) decreased. Conclusion: The Lean A3 method is a successful quality improvement tool for improving and sustaining opioid prescribing within a single academic rheumatology clinic. This method has potential applicability to similar clinics interested in improving opioid prescribing.